1985
DOI: 10.1007/bf00704370
|View full text |Cite
|
Sign up to set email alerts
|

Aortic intimal monocyte recruitment in the normo and hypercholesterolemic baboon (Papio cynocephalus)

Abstract: The ultrastructural features of peripheral blood monocyte margination, migration, and aortic intimal accumulation have been described in the normo- and mildly hypercholesterolemic baboon. Intimal monocyte-macrophage recruitment over fatty streaks and fibro-fatty plaques was enhanced by dietary cholesterol-fat supplementation, resulting in an 8-fold increase in monocyte-macrophages and macrophage-derived foam cells in the subendothelial space. Margination or attachment observed over both plaques and normal area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(20 citation statements)
references
References 29 publications
3
17
0
Order By: Relevance
“…This may result in the local accumulation of monocytes within the vessel wall. Such a process would have direct relevance for the increased incidence of atherosclerosis in diabetes, as intimal monocyte recruitment is thought to be an important early step in the pathogenesis of atherosclerosis [25]. The adhesion of activated monocytes to AGE-proteins within the vessel wall may result in the remodelling of vessel structure following protease secretion [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…This may result in the local accumulation of monocytes within the vessel wall. Such a process would have direct relevance for the increased incidence of atherosclerosis in diabetes, as intimal monocyte recruitment is thought to be an important early step in the pathogenesis of atherosclerosis [25]. The adhesion of activated monocytes to AGE-proteins within the vessel wall may result in the remodelling of vessel structure following protease secretion [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…Restoration of migratory capacity was accompanied by alterations in the cytoskeleton system, especially in actin arrangement are a major constituent of the atherosclerotic plaque and play an important role in the development of the lesion. 1 " 4 In vitro studies have shown that modified forms of low density Lipoprotein (LDL) cause accumulation of cholesterol esters in cultured macrophages, 5 " 9 whereas normal LDL does not result in significant lipid accumulation within these cells. 5 Steinberg et al 10 have reported that LDL is converted by endothelial cells or chemical oxidation with Cu 2+ into a negatively charged form, which is avidly taken up by macrophages via the scavenger receptor.…”
Section: A Mechanism For Atherosclerosis Regression?mentioning
confidence: 99%
“…The role of monocytes in the pathogenesis of atherosclerosis is well recognized and the adhesion of blood-borne monocytes to the endothelium of lesion-prone regions of the vasculature is one of the earliest documented events in numerous animal mod-els of atherosclerosis (1)(2)(3)(4)(5)(6)(7). Altered or dysfunctional endothelium expresses a number of cytokines, adhesion molecules, vasoactive compounds, and growth factors, which in turn attract, activate, and cause the transendothelial migration of monocytes (8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%